ADHERENCE TO INSULIN IN SINGAPOREAN PEDIATRIC TYPE 1 DIABETES PATIENTS AND ITS IMPACT ON GLYCEMIC CONTROL AND HEALTH-CARE UTILIZATION - BRANDON WEN BING CHUA; XIN YAN LIM; KAR MEN POH; JAMIE STEPHANIE CALEB; MCVIN HUA HENG CHEEN; SOO TING LIM; NGEE LEK (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Optimizing glycemic control is challenging with insulin non-adherence. This study aimed to characterize the prevalence of non-adherence among Singaporean pediatric patients with type 1 diabetes mellitus (T1DM) and investigate its associated outcomes. Methods: Singaporean patients with T1DM aged ≤18 years old with ≥1 year of insulin prescription between 2012 and 2016 were included in this retrospective, single-center longitudinal study. Patients on insulin pumps were excluded from the study. Non-adherence was defined as medication possession ratio (MPR) <100%. Glycemic control was defined using mean hemoglobin A1c (HbA1c) within the study period. Health-care utilization was defined as the number of outpatients, inpatient, and emergency visits. The t-test, Chi-square test, logistic regression, and Poisson regression were used to analyze means, proportions, factors associated with non-adherence, and association of non-adherence and health-care utilization, respectively. Sensitivity analyses were performed for MPR thresholds of 80% and 95%. Results: A total of 206 patients were included in this study. Non-adherent patients were older, had a longer duration of diabetes since diagnosis and shorter duration of follow-up. Gender, race, financial class, and number of concurrent medications were comparable between groups. The prevalence of non-adherence was 34.0% (95% confidence interval [CI]: 27.9–40.7%). Non-adherent patients had a higher average HbA1c (non-adherent: 9.6% [2.1] vs. adherent: 8.6% [1.3], p<0.001). Non-adherence was not associated with health-care utilization. Patients with >5 years of diabetes were more likely to be non-adherent. Conclusion: Non-adherence defined as MPR <100% is associated with poorer glycemic control. Further interventions may focus on patients with >5 years of diabetes to improve their adherence to insulin therapy.